N-(4-Bromophenyl)-2-(naphthalen-1-yl)acetamide - Fun, Hoong-Kun (International Union of Crystallography, 2011)
In the title compound, C(18)H(14)BrNO, the naphthalene ring system and the benzene ring form dihedral angles of 78.8 (2) and 19.7 (2)°, respectively, with the acetamide C—C(=O)—N plane. The naphthalene ring system forms a dihedral angle of 64.88 (19)° with the benzene ring. In the crystal, molecules are linked via intermolecular bifurcated (N,C)—H⋯O hydrogen bonds, generating an R (2) (1)(6) ring motif, forming chains along the b axis.